A NOVEL UV-SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION OF DOLUTEGRAVIR IN BULK AND ITS LABORATORY SYNTHETIC MIXTURE BY USING 8 M UREA AS HYDROTROPIC SOLUBILIZING AGENT (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The term hydrotropy has been used to designate the increase in solubility in water of various substances due to the presence of large amount of additives. Concentrated aqueous hydrotropic solutions of sodium benzoate, urea, nicotinamide, sodium salicylate, sodium ascorbate and sodium glycinate have been observed to enhance the aqueous solubility of many poorly water-soluble drugs. In the present investigation hydrotropic solubilization technique has been employed to solubilize the poorly water-soluble anti retroviral drug, Dolutegravir. Determination of solubilities of the drug in 8 M urea hydrotropic solution and distilled water was carried out at room temperature. There was more than 50-fold enhancement in aqueous solubility of Dolutegravir with 8 M urea (as compared to aqueous solubility). Therefore, it was thought worthwhile to solubilize the poorly water-soluble Dolutegravir from fine powder of its laboratory mixture to carryout spectrophotometric analysis at 258 nm in method A, 248-268 nm in method B and 256 nm in method C. urea does not show any absorbance above 250 nm. Beerۥs law was obeyed in the concentration range of 52.5-20µg/ml in method A, B and C, with correlation coefficients (R) of 0.996, 0.995 and 0.996 respectively. Laboratory mixture containing piroxicam have been analyzed successfully. Recovery studies and statistical data proved the accuracy, reproducibility and the precision of the proposed method. Based on the same principle a large number of drugs having λmax above 250 nm can be estimated by 8 M urea (inexpensive hydrotropic agent). Thus, hydrotropic solutions can be used in place of organic solvents (which are pollutants, toxic and give error due to volatility).